If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + y) + 1x + 6y = 0 (x * 2 + y * 2) + 1x + 6y = 0 (2x + 2y) + 1x + 6y = 0 Reorder the terms: 2x + 1x + 2y + 6y = 0 Combine like terms: 2x + 1x = 3x 3x + 2y + 6y = 0 Combine like terms: 2y + 6y = 8y 3x + 8y = 0 Solving 3x + 8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. 3x + 8y + -8y = 0 + -8y Combine like terms: 8y + -8y = 0 3x + 0 = 0 + -8y 3x = 0 + -8y Remove the zero: 3x = -8y Divide each side by '3'. x = -2.666666667y Simplifying x = -2.666666667y
| -6a-11=13 | | 7(x-5)-4=-3(-8x+9)-7x | | 7x-15y=-126 | | 360-3x/360 | | -44+r=-51 | | -7(w+1)=-3(8w-3)+7w | | 5v+x= | | 4z+8=38 | | 20x^2+224x-3840=0 | | ((4m^2)(3n^5))/((2m^-3)(-mn)^3) | | 0.5x+0.2=0.7x-1.6 | | 5+(7+v)=20 | | -2(y-12)=y-9 | | -4+t=38 | | 5x^2+56x-960=0 | | 1/3t−4/3=−5/4t−3/2 | | 30/1=144/x | | 2-(y+12)=y-9 | | 75+50x=70x | | =3(3x+3y+3) | | 0.11-0.01(x+3)=-0.01(2-x) | | (19m/5)-(3/5)=-1.4-(m/5) | | 6-(5+4i)-(-13-I)= | | y=8mx+2b | | 7+12y=24y-1 | | |3/4| | | 8a=12a-7b-9b-11a | | 24x-12y=40 | | 4x+1x=3+x | | -1third=r-3fourths | | V=-9+2v | | 9x-3x+8=x-8+16 |